Problems of ensuring the competitiveness of the region in the conditions of COVID-19 - Pashkus Vadim; Volkova Anna; Maltseva Yulia (SHS Web of Conferences, 2021)
Research background: In the context of the COVID-19 pandemic and its global consequences, a fundamentally different economic environment arises, which requires the use of new approaches to the formation of the economic policy of the region and the identification of new ways to ensure the global competitiveness of the region. Territories are beginning to compete for previously unclaimed resources, as well as use new methods of promotion and positioning. Purpose of the article: The purpose of this work is to identify new economic conditions caused by the COVID-19 pandemic and its consequences, as well as to assess the impact of these conditions on the effectiveness of the economic policy of the region and the applied promotion and positioning strategy. Methods: The methods of this study are determined by the increasing level of uncertainty of regional development processes, which requires the adaptation of analysis tools. The work uses matrix and hierarchical research methods that allow for a qualitative analysis of problem situations. Findings & Value added: The research carried out made it possible to identify and systematize the main characteristics of the new economic environment and assess its impact on the applied development strategy of the region, which guarantees a higher probability of achieving strategic competitiveness. The novelty of the study lies also in the recognition of the mobilization effect of “forced digitalization”, while in the context of a pandemic, this mobilization was based on stable (stereotypical) interaction practices.